CREATIVENESS AND CREATIVENESS IN A PERSON THE NEED FOR THE DEVELOPMENT OF ADJECTIVES - Yakubova Barno Bakhtiyarovna (Journals Park Publishing, 2022)
The article outlines such important pedagogical tasks as the development of creative features of personality in order to ensure its improvement in the era of socio-economic relations, as well as tasks related to the organization of such a process in a new interpretation.
Keywords: personality; creativity; creative qualities